Annie Besant’s sexual politics of marriage in Victorian England (2009)
Victorian sexuality has often been regarded as the epitome of prudery and chastity, as a reflection of a period which placed great emphasis on the control of sexuality and women’s body as way to maintain and ensure social and cultural control. Nonetheless, this modernist conceptualisation was gradually left behind when mid-twentieth century historians and theorists looked back to the past to recover the complexity of a period of contrasts which both preached the ethics of prudery and virtuosity, while the overwhelming increase of population remained a plain fact. The aim of this essay is to reassess assumptions of Victorian sexualities through Annie Besant’s works and ideas as regards marriage policies in an attempt to shed light over contemporary Neo-Victorian conceptions of sexualities, thus restoring Besant’s position as a canonical figure at the end of nineteenth-century Victorian feminism.